Development of Animation Video on the Blood Circulatory System Materials as Self Study Media - Mujahidah, Mawar Intan; Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to develop animated video products, determine the quality of animated video products, and determine student responses to animated video products developed as a form of self-study media on the material of the blood circulatory system. This research is a research and development research and development (R&D) with a development model developed by Sugiyono by following six steps, namely: potential and problem analysis, data and information collection, product design, design validation, design revision and product testing. The assessment instrument used is a questionnaire sheet to determine product quality and student responses to animated videos on the material of the blood circulatory system. Products were assessed by 1 material expert, 1 media expert, 5 reviewers, and 1 biology teacher. The product trial was limited to 15 high school students in class XI to determine student responses. Based on product quality assessments from material experts, the ideal percentage results are 91.1% with very good category, media expert assessments get 80% ideal percentage results in good categories, assessments from peer reviewers get ideal percentage results of 89.7% in very good categories, Biology teacher’s assessment got the ideal percentage result of 92.3% with very good category. The assessment of all reviewers of the animated video learning media on the blood circulatory system material shows an average ideal percentage of 88.9% which is included in the very good category, while product trials on student responses get an assessment percentage of 99.6% with the category strongly agree. Thus, the results of this study indicate that the animated video on the circulatory system material that has been developed is feasible to be used as an self-study media.